LGBT Agenda in Kazakhstan: Social and Psychological Aspect - Matrassulova, Dinara; Massalimova, Aliya; Bakirov, Akhat; Vitulyova, Yelizaveta; Suleimenov, Ibragim (Journal of Ecohumanism, 2024)
The article defends the point of view according to which the increased acuteness of discussions around the LGBT agenda in Kazakhstan is due to the competition of several different socio-cultural codes, the bearers of which are citizens of Kazakhstan. It is proved that the existence of such competition is objective and is due to historical reasons. It is shown that the genesis of the widespread LGBT views reflects, among other things, the crisis of the classical monogamous family, which occurs for objective reasons. The main one of these reasons is the growing difference between the ages of social and biological maturation. It is shown that this crisis, among other things, gives rise to numerous psychological problems, forcing the population of Kazakhstan to increasingly turn to the services of practicing psychologists and psychoanalysts. It is shown that the resolution of accumulated contradictions can be realized through the introduction of modernized concepts in Kazakhstan that meet DEI. At the same time, the modernization of DEI should be based on the need to harmonize various socio-cultural codes on the platform of solving the geopolitical problems facing the Republic of Kazakhstan.